Immunological biomarkers and molecular signatures in healthy aging: early dynamics of subclinical atherosclerosis in a homogeneous elderly cohort - Weyh, Christopher; Bauer, Pascal; Größer, Vincent Walter; Zhupani, Danja; Cemic, Franz; Huber, Magdalena; Raifer, Hartmann; Mahnke, Marius; Frech, Torsten; Böttrich, Tim; Gebhardt, Kristina; Nolte, Svenja; et al. (My University, 2025)
Background: The study aimed to investigate early immunological and molecular changes in a homogeneous group of healthy older individuals, initially screened to categorize them into groups with or without subclinical carotid artery plaque. Subsequently, immunological and molecular signatures, vascular health parameters, and lifestyle factors were assessed, and a comprehensive bioinformatics analysis was conducted to identify biomarkers for predicting subclinical atherosclerosis. Methods: The present study was performed in 79 healthy participants (male: n = 50; age = 63.6 ± 3.7 years; body mass index = 24.9 ± 3.1 kg/m²; mean ± SD). Participants were categorized according to subclinical atherosclerotic plaque (SAP) status by ultrasound of the carotids. This was followed by a comprehensive analysis using T-cell phenotyping, serum protein signature and gene expression analysis, vascular assessment, analysis of physical activity and capacity as well as food intake. Results: Percentage of CD4⁺-naïve T-cells are the variable with the strongest negative association with the plaque group. Among the top 10 variables, CD4−CD8− lymphocytes are also negatively associated with SAP. In contrast, CD8+ CM T-cells were found positively associated with SAP. LaminB1, tumor protein 53 and systolic blood pressure, central systolic blood pressure, vascular age, osteopontin, and CD4⁺ CM T-cells were also positively associated with SAP. Conclusion: Despite a rather homogeneous cohort of elderly participants with high cardiorespiratory fitness, we have associated various cellular and molecular signatures with the presence of SAP. Significant associations with SAP were shown by known markers of immunosenescence. These results underline the relevance of immunological biomarkers in the detection of subclinical atherosclerosis.
Keywords: ddc:796